High-thermal-conductivity wear-resistant high-performance polytetrafluoroethylene plastic
By using modified graphene oxide filler in polytetrafluoroethylene plastics, combined with electrophoretic deposition method and ion beam bombardment technology, the problems of poor thermal conductivity, insufficient wear resistance and lack of hydrophobicity of polytetrafluoroethylene plastics are solved, and the effects of high thermal conductivity, wear resistance and hydrophobicity are achieved.
Patent Information
- Application Number
- CN202411451745.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In practical applications, polytetrafluoroethylene plastics have problems such as poor thermal conductivity, insufficient wear resistance and lack of hydrophobicity, which limits their application in high demand occasions.
Modified graphene oxide was used as filler, mixed with polytetrafluoroethylene and cold pressed, and an outer composite film was made. Modified graphene oxide is mixed with boron nitride and carboxylated graphene after fumigation alkali treatment, and a silane coupling agent is used to assist grinding with supercritical carbon dioxide fluid to improve its thermal conductivity and wear resistance. Then, a magnesium oxide film was added by electrophoretic deposition method, and the hydrophobicity was improved by ion beam bombardment.
It achieves high thermal conductivity, wear resistance and hydrophobic effects, improves the overall performance of PTFE plastics, making them more suitable for high-demand applications.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastics, in particular to a high-heat-conductivity, wear-resistant and high-performance polytetrafluoroethylene plastic. Background Art
[0002] As a primary plastic, polytetrafluoroethylene (PTFE) possesses several excellent properties, such as chemical inertness and high-temperature resistance. However, PTFE also has drawbacks, such as low strength, low hardness, high wear rate, significant viscoelastic deformation under external forces, and poor thermal conductivity, which limit its practical application. To adapt it for use in demanding applications, PTFE must be appropriately modified. Adding fillers is a simple and effective method. Adding different fillers to PTFE can significantly alter its physical and mechanical properties.
[0003] Graphene oxide has excellent thermal conductivity, but it struggles to balance hydrophobicity and wear resistance. Graphene oxide's inherently rich active groups make it hydrophilic, but its layered structure makes it susceptible to wear. Furthermore, when added to plastics as a filler, it easily agglomerates due to van der Waals forces, impacting performance. Therefore, the present invention addresses these issues by creating a highly thermally conductive, wear-resistant, and high-performance polytetrafluoroethylene plastic using graphene oxide as a filler. Summary of the Invention
[0004] The purpose of the present invention is to provide a high-thermal-conductivity, wear-resistant and high-performance polytetrafluoroethylene plastic and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a high thermal conductivity, wear-resistant and high-performance polytetrafluoroethylene plastic, wherein the high thermal conductivity, wear-resistant and high-performance polytetrafluoroethylene plastic is filled with modified graphene oxide, mixed with polytetrafluoroethylene and cold-pressed, and then coated with a composite film.
[0006] Furthermore, the modified graphene oxide is prepared by mixing modified boron nitride after alkali fumigation with carboxylated graphene, and grinding is assisted by a silane coupling agent and supercritical carbon dioxide fluid.
[0007] Furthermore, a method for preparing high-thermal-conductivity, wear-resistant, and high-performance polytetrafluoroethylene plastic comprises the following steps: (1) Add 2-4 parts of boron nitride to 20 parts of deionized water, stir at 200-300 r / min for 20 minutes, and ultrasonically treat at 80°C, 150W, and 40kHz. At the same time, spray gaseous sodium hydroxide solution for 40-60 minutes, wash with deionized water three times, and dry at a vacuum degree of 20 Pa and 60°C for 5 hours to obtain modified boron nitride; (2) 10-12 parts of graphene oxide and 20 parts of deionized water were ultrasonically dispersed at 100W and 30kHz for 1 hour, 0.2-0.4 parts of methyl bromoacetate were added, and ultrasonically dispersed under the same conditions for 15 minutes. The reaction was continued for 5 hours, and the filtrate was filtered and washed with deionized water three times. The filtrate was dried at a vacuum degree of 20Pa and 50°C for 2-3 hours to obtain carboxylated graphene; (3) Disperse 0.1-0.6 parts of carboxylated graphene and 0.1-0.3 parts of modified boron nitride in 20 parts of solvent, ultrasonicate at 1000-1800W for 0.5-3h, centrifuge at 3000-5000rpm for 0.5-1h, and take solid precipitate to obtain the composite material; put 10 parts of the composite material into a ball mill, add 0.2-0.6 parts of 3-triethoxysilyl-1-propylamine three times, add one third of the total amount each time, and add once every 6h to obtain the composite material. Zirconia is used as a grinding ball medium, and after ball milling at 500 r / min for 18 hours, it is dried at 25°C for 12 hours to obtain a ball-milled product; 5 parts of the ball-milled product are mixed with 1-2 parts of a methanol solution and stirred at 400-600 r / min for 20 minutes, placed in a 35°C oil bath, filled with carbon dioxide, and heated and pressurized to 120°C and 6.5 MPa. After reacting for 2 hours, it is cooled to room temperature, and the precipitate is taken, washed with methanol 5 times, and dried at 60°C and a vacuum degree of 20 Pa for 6 hours to obtain modified graphene oxide; (4) 12-16 parts of polytetrafluoroethylene and 1-2 parts of modified graphene oxide were stirred at 1000-2000 r / min for 30 minutes, cold pressed, and then placed in a mold at 360-380°C, pressurized to 150-170 MPa, sintered for 2 hours, and then cooled to 80-100°C. The mold was taken out and naturally cooled to 25°C to form a plastic cube of 1 cm × 1 cm × 1 cm; (5) Take 0.1-0.3 parts of magnesium oxide, 6 parts of ethanol, 0.4-0.8 parts of cerium nitrate, and 0.1-0.3 parts of dodecyltrimethoxysilane, and after ultrasonication for 30 minutes, obtain an electrophoretic suspension; immerse the plastic block in the electrophoretic suspension, use the Au sheet as the anode and the Si substrate as the cathode, and perform electrophoretic deposition for 3 minutes at a voltage of 200V and a distance between the anode and cathode of 2cm. Dry at 60℃ for 3 hours. While drying, bombard the membrane surface with argon ions to obtain high-performance polytetrafluoroethylene plastic with high thermal conductivity and wear resistance.
[0008] Furthermore, in step (1), the flow rate of spraying sodium hydroxide is 2-6 mL / min, and the mass fraction of the sodium hydroxide solution is 10%.
[0009] Furthermore, the solvent in step (3) is a mixture of one or more of isopropyl alcohol, N-methylpyrrolidone or N,N-dimethylformamide.
[0010] Furthermore, the material-to-ball ratio in the ball milling in step (3) is 1:10.
[0011] Furthermore, the methanol solution in step (3) is a mixed solution of methanol and deionized water in a mass ratio of 4:1.
[0012] Furthermore, the ultrasonic conditions in step (5) are 500W and 30kHz.
[0013] Furthermore, the ion beam energy in step (5) is 1 keV.
[0014] Furthermore, in step (5), the incident angle of the ion beam is 45° to the normal of the substrate plane.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses boron nitride modified graphene oxide as filler, melt-extrudes the plastic with polytetrafluoroethylene, and then electroplates a magnesium oxide film to achieve high thermal conductivity, wear resistance, and hydrophobicity.
[0016] First, the present invention performs alkali fumigation treatment on boron nitride, and simultaneously uses ultrasonic microwaves and a gas-phase alkaline solution to infiltrate and modify the boron nitride under the action of ultrasound, thereby enriching the surface of the boron nitride with hydroxyl groups; then, methyl bromoacetate is used to modify graphene oxide to prepare carboxylated graphene, which is then mixed with the modified boron nitride and ground; a silane coupling agent is continuously added during the grinding process to reduce friction and improve wear resistance; and then a second grinding is performed with the aid of supercritical carbon dioxide, so that the boron nitride and the graphene oxide are more firmly and evenly combined, and the phenomenon that the graphene oxide is easily agglomerated is improved, thereby improving the performance of the plastic.
[0017] Secondly, the modified graphene oxide is mixed with polytetrafluoroethylene and cold-pressed into plastic. A magnesium oxide film is produced on the plastic surface using electrophoretic deposition. Dodecyltrimethoxysilane and electrolyte cerium nitrate are added to the electrolyte solution to react together to form cerium dioxide, which seals the microcracks in the coating to achieve a wear-resistant effect. The silane makes the surface of the composite coating have many short, rod-like protrusions, thereby achieving a hydrophobic effect. The surface of the modified film is then bombarded with an ion beam to increase the density of the film, further improving the hydrophobicity and wear resistance of the film. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0019] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various indicators of the high thermal conductivity, wear-resistant and high-performance polytetrafluoroethylene plastics prepared in the following examples. Wear resistance: A GCrl5 bearing steel ball with a diameter of 10 mm was used to slide on the specimen. The sliding reciprocating stroke was 6 mm, the time was 20 min, the reciprocating frequency was 10 Hz, and the load was F = 10 N. All friction and wear tests were carried out at 20 ° C and repeated 3 times. The average value was taken as the wear rate of the material.
[0020] Hydrophobicity: The material is tested based on the sessile drop method and the contact angle of the drop is measured using a surface contact angle meter.
[0021] Thermal conductivity: Take the coating material of the same thickness and test the thermal conductivity of the coating according to the standard ASTMD5470 Example 1 (1) Add 2 parts of boron nitride to 20 parts of deionized water, stir at 200 r / min for 20 min, and ultrasonically treat at 80°C, 150 W, and 40 kHz. At the same time, spray gaseous sodium hydroxide solution at a flow rate of 2 mL / min and a mass fraction of 10% for 40 min. Wash with deionized water three times and dry at a vacuum degree of 20 Pa and 60°C for 5 h to obtain modified boron nitride. (2) 10 parts of graphene oxide and 20 parts of deionized water were ultrasonically dispersed at 100 W and 30 kHz for 1 hour, 0.2 parts of ethyl methyl bromide were added, and ultrasonically dispersed under the same conditions for 15 minutes. The reaction was continued for 5 hours, and the filtrate was filtered and washed with deionized water three times. The vacuum degree was 20 Pa and the temperature was dried at 50 ° C for 2 hours to obtain carboxylated graphene; (3) Take 0.1 parts of carboxylated graphene and 0.1 parts of modified boron nitride and disperse them in 20 parts of isopropanol. After ultrasonication at 1000W for 0.5h, centrifuge at 3000rpm for 0.5h, and take the solid precipitate to obtain the composite material. Put 10 parts of the composite material into a ball mill and add 0.2 parts of 3-triethoxysilyl-1-propylamine three times, adding one third of the total amount each time, and adding once every 6 hours. Use zirconium oxide as the ball medium, 500r / min, and a material-ball ratio of 1:1. After ball milling at 0 for 18 hours, it was dried at 25°C for 12 hours to obtain a ball-milled product; 5 parts of the ball-milled product were mixed with 1 part of a methanol solution, in which the mass ratio of methanol to deionized water was 4:1, and stirred at 400 r / min for 20 minutes. The mixture was placed in a 35°C oil bath, filled with carbon dioxide, and heated and pressurized to 120°C and 6.5 MPa. After reacting for 2 hours, the mixture was cooled to room temperature, and the precipitate was washed with methanol 5 times, and dried at 60°C and a vacuum degree of 20 Pa for 6 hours to obtain modified graphene oxide; (4) After 12 parts of polytetrafluoroethylene and 1 part of modified graphene oxide were stirred at 1000 r / min for 30 minutes, cold pressed at 0°C, and then placed in a mold at 360°C, pressurized to 150 MPa, sintered for 2 hours, cooled to 80°C, taken out, and naturally cooled to 25°C to form a plastic cube of 1 cm × 1 cm × 1 cm; (5) Take 0.1 parts of magnesium oxide, 6 parts of ethanol, 0.4 parts of cerium nitrate, and 0.1 parts of dodecyltrimethoxysilane, and after ultrasonication at 500W and 30kHz for 30 minutes, an electrophoretic suspension is obtained; the plastic cube is immersed in the electrophoretic suspension, and an Au sheet is used as the anode and a Si substrate is used as the cathode. Electrophoretic deposition is performed at a voltage of 200V and a distance between the cathode and the anode of 2cm for 3 minutes, and then dried at 60℃ for 3 hours. While drying, the film surface is bombarded with argon ions. The incident angle of the ion beam is 45° to the normal of the substrate plane, and the ion beam energy is 1keV, thereby obtaining high-performance polytetrafluoroethylene plastic with high thermal conductivity and wear resistance.
[0022] Example 2 (1) Add 3 parts of boron nitride to 20 parts of deionized water, stir at 250 r / min for 20 min, and ultrasonically treat at 80°C, 150 W, and 40 kHz. At the same time, spray gaseous sodium hydroxide solution at a flow rate of 4 mL / min and a mass fraction of 10% for 50 min. Then wash with deionized water three times and dry at a vacuum degree of 20 Pa and 60°C for 5 h to obtain modified boron nitride. (2) 11 parts of graphene oxide and 20 parts of deionized water were ultrasonically dispersed at 100 W and 30 kHz for 1 hour, 0.3 parts of methyl bromoacetate were added, and ultrasonically dispersed under the same conditions for 15 minutes. The reaction was continued for 5 hours, and the filtrate was filtered and washed with deionized water three times. The vacuum degree was 20 Pa and the temperature was dried at 50 ° C for 2.5 hours to obtain carboxylated graphene; (3) Take 0.3 parts of carboxylated graphene and 0.2 parts of modified boron nitride and disperse them in 20 parts of N-methylpyrrolidone solvent. After ultrasonication at 1400W for 1.75h, centrifuge at 4000rpm for 0.75h, and take the solid precipitate to obtain the composite material. Put 10 parts of the composite material into a ball mill and add 0.4 parts of 3-triethoxysilyl-1-propylamine three times, adding one third of the total amount each time, and adding once every 6h. Use zirconium oxide as the grinding ball medium, 500r / min, and a material-ball ratio of After ball milling at 1:10 for 18 hours, the mixture was dried at 25°C for 12 hours to obtain a ball-milled product; 5 parts of the ball-milled product were mixed with 1.5 parts of a methanol solution, wherein the mass ratio of methanol to deionized water in the methanol solution was 4:1, and stirred at 500 r / min for 20 minutes. The mixture was placed in a 35°C oil bath, filled with carbon dioxide, and heated and pressurized to 120°C and 6.5 MPa. After reacting for 2 hours, the mixture was cooled to room temperature, the precipitate was taken, washed with methanol 5 times, and dried at 60°C and a vacuum degree of 20 Pa for 6 hours to obtain modified graphene oxide; (4) 14 parts of polytetrafluoroethylene and 1.5 parts of modified graphene oxide were stirred at 1500 r / min for 30 min, cold pressed at 2.5 °C, then placed in a mold at 370 °C, pressurized to 160 MPa, sintered for 2 h, cooled to 90 °C, taken out, and naturally cooled to 25 °C to form a plastic cube of 1 cm × 1 cm × 1 cm; (5) Take 0.2 parts of magnesium oxide, 6 parts of ethanol, 0.6 parts of cerium nitrate, and 0.2 parts of dodecyltrimethoxysilane, and after ultrasonication at 500W and 30kHz for 30 minutes, an electrophoretic suspension is obtained; the plastic block is immersed in the electrophoretic suspension, and an Au sheet is used as the anode and a Si substrate is used as the cathode. Electrophoretic deposition is performed at a voltage of 200V and a distance between the cathode and the anode of 2cm for 3 minutes, and the block is dried at 60℃ for 3 hours. While drying, the membrane surface is bombarded with argon ions. The incident angle of the ion beam is 45° to the normal of the substrate plane, and the ion beam energy is 1keV. High-performance polytetrafluoroethylene plastic with high thermal conductivity and wear resistance is obtained.
[0023] Example 3 (1) Add 4 parts of boron nitride to 20 parts of deionized water, stir at 300 r / min for 20 minutes, and ultrasonically treat at 80°C, 150W, and 40kHz. At the same time, spray gaseous sodium hydroxide solution at a flow rate of 6 mL / min and a mass fraction of 10% for 60 minutes. Wash with deionized water three times and dry at a vacuum degree of 20 Pa and 60°C for 5 hours to obtain modified boron nitride. (2) 12 parts of graphene oxide and 20 parts of deionized water were ultrasonically dispersed at 100 W and 30 kHz for 1 hour, 0.4 parts of methyl bromoacetate were added, and ultrasonically dispersed under the same conditions for 15 minutes. The reaction was continued for 5 hours, and the filtrate was filtered and washed with deionized water three times. The filtrate was dried at a vacuum degree of 20 Pa and 50 ° C for 3 hours to obtain carboxylated graphene; (3) Take 0.6 parts of carboxylated graphene and 0.3 parts of modified boron nitride and disperse them in 20 parts of N,N-dimethylformamide solvent. After ultrasonication at 1800W for 3 hours, centrifuge at 5000rpm for 1 hour, and take the solid precipitate to obtain the composite material; put 10 parts of the composite material into a ball mill, add 0.6 parts of 3-triethoxysilyl-1-propylamine three times, add one third of the total amount each time, and add once every 6 hours, use zirconium oxide as the grinding ball medium, 500r / min, and a material-ball ratio of 1 :10 for 18 hours, and then dried at 25°C for 12 hours to obtain a ball-milled product; take 5 parts of the ball-milled product and 2 parts of a methanol solution, wherein the mass ratio of methanol to deionized water in the methanol solution is 4:1, and stir at 600r / min for 20 minutes, place in a 35°C oil bath, fill with carbon dioxide, increase the temperature and pressure to 120°C and 6.5MPa, react for 2 hours, cool to room temperature, take the precipitate, wash it with methanol 5 times, and dry it at 60°C and a vacuum degree of 20Pa for 6 hours to obtain modified graphene oxide; (4) After 16 parts of polytetrafluoroethylene and 2 parts of modified graphene oxide were stirred at 2000 r / min for 30 minutes, cold pressed at 5°C, and then placed in a mold at 380°C, pressurized to 170 MPa, sintered for 2 hours, cooled to 100°C, taken out, and naturally cooled to 25°C to form a plastic cube of 1 cm × 1 cm × 1 cm; (5) Take 0.3 parts of magnesium oxide, 6 parts of ethanol, 0.8 parts of cerium nitrate, and 0.3 parts of dodecyltrimethoxysilane, and after ultrasonication at 500W and 30kHz for 30 minutes, an electrophoretic suspension is obtained; the plastic block is immersed in the electrophoretic suspension, and an Au sheet is used as the anode and a Si substrate is used as the cathode. Electrophoretic deposition is performed at a voltage of 200V and a distance between the cathode and the anode of 2cm for 3 minutes, and the block is dried at 60℃ for 3 hours. While drying, the membrane surface is bombarded with argon ions. The incident angle of the ion beam is 45° to the normal of the substrate plane, and the ion beam energy is 1keV. High-performance polytetrafluoroethylene plastic with high thermal conductivity and wear resistance is obtained.
[0024] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that there is no step (1), and step (3) is changed to: 0.3 parts of carboxylated graphene and 0.2 parts of boron nitride are dispersed in 20 parts of N-methylpyrrolidone, ultrasonicated at 1400W for 1.75 hours, centrifuged at 4000rpm for 0.75 hours, and solid precipitate is taken to obtain a composite material; 10 parts of the composite material are placed in a ball mill, and 0.4 parts of 3-triethoxysilyl-1-propylamine are added three times, each time adding one-third of the total amount, and once every 6 hours, using zirconium oxide as the grinding ball medium, 500r / m After ball milling for 18 hours at a material-to-ball ratio of 1:10, the mixture was dried at 25°C for 12 hours to obtain a ball-milled product; 5 parts of the ball-milled product and 1.5 parts of a methanol solution, wherein the mass ratio of methanol to deionized water in the methanol solution is 4:1, were stirred at 500 r / min for 20 minutes, placed in a 35°C oil bath, charged with carbon dioxide, and heated and pressurized to 120°C and 6.5 MPa. After reacting for 2 hours, the mixture was cooled to room temperature, the precipitate was taken, washed 5 times with methanol, and dried at 60°C and a vacuum degree of 20 Pa for 6 hours to obtain modified graphene oxide; the remaining steps were the same as in Example 2.
[0025] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that there is no step (2), and step (3) is changed to: 0.3 parts of graphene oxide and 0.2 parts of modified boron nitride are dispersed in 20 parts of N-methylpyrrolidone solvent, ultrasonicated at 1400W for 1.75 hours, centrifuged at 4000rpm for 0.75 hours, and solid precipitate is taken to obtain a composite material; 10 parts of the composite material are placed in a ball mill, and 0.4 parts of 3-triethoxysilyl-1-propylamine are added three times, each time adding one third of the total amount, and once every 6 hours, using zirconium oxide as the grinding ball medium, 500r / min, a material-ball ratio of 1:10, and ball milling for 18 h, followed by drying at 25 ° C for 12 h to obtain a ball-milled material; 5 parts of the ball-milled material and 1.5 parts of a methanol solution, wherein the mass ratio of methanol to deionized water in the methanol solution is 4:1, are stirred at 500 r / min for 20 min, placed in a 35 ° C oil bath, filled with carbon dioxide, and heated and pressurized to 120 ° C and 6.5 MPa. After reacting for 2 h, the mixture is cooled to room temperature, the precipitate is taken, washed with methanol 5 times, and dried at 60 ° C and a vacuum degree of 20 Pa for 6 h to obtain modified graphene oxide; the remaining steps are the same as in Example 2.
[0026] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that step (3) is different. Step (3) is changed to: 0.3 parts of carboxylated graphene and 0.2 parts of modified boron nitride are dispersed in 20 parts of N-methylpyrrolidone solvent, ultrasonicated at 1400W for 1.75h, centrifuged at 4000rpm for 0.75h, and solid precipitate is taken to obtain a composite material; 10 parts of the composite material are put into a ball mill, and milled for 18h at 500r / min and a material-ball ratio of 1:10 with zirconium oxide as the grinding ball medium, and 25 ℃ and dried for 12 hours to obtain a ball-milled product; 5 parts of the ball-milled product and 1.5 parts of a methanol solution, wherein the mass ratio of methanol to deionized water in the methanol solution is 4:1, are stirred at 500 r / min for 20 minutes, placed in a 35℃ oil bath, charged with carbon dioxide, and heated and pressurized to 120℃ and 6.5 MPa. After reacting for 2 hours, the product is cooled to room temperature, and the precipitate is taken, washed with methanol 5 times, and dried at 60℃ and a vacuum degree of 20 Pa for 6 hours to obtain modified graphene oxide; the remaining steps are the same as those in Example 2.
[0027] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that step (3) is different. Step (3) is changed to: take 0.3 parts of carboxylated graphene and 0.2 parts of modified boron nitride and disperse them in 20 parts of N-methylpyrrolidone solvent, ultrasonicate at 1400W for 1.75 hours, centrifuge at 4000rpm for 0.75 hours, and take solid precipitate to obtain a composite material; put 10 parts of the composite material into a ball mill, add 0.4 parts of 3-triethoxysilyl in three times, add one third of the total amount each time, and add once every 6 hours, use zirconium oxide as the grinding ball medium, ball mill for 18 hours at 500r / min and a material-ball ratio of 1:10, and then dry at 25°C for 12 hours to obtain modified graphene oxide; the remaining steps are the same as Example 2.
[0028] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that step (5) is different. Step (5) is changed to: take 0.2 parts of magnesium oxide, 6 parts of ethanol, and 0.2 parts of dodecyltrimethoxysilane, and obtain an electrophoretic suspension after 30 minutes of ultrasound at 500W and 30kHz; immerse the plastic block in the electrophoretic suspension, use an Au sheet as the anode and a Si substrate as the cathode, electrophoretically deposit for 3 minutes at a voltage of 200V and a cathode-anode distance of 2cm, and dry at 60°C for 3 hours. While drying, bombard the film surface with argon ions, the incident angle of the ion beam and the normal to the substrate plane are 45°, and the ion beam energy is 1keV, thereby obtaining a high-thermal-conductivity, wear-resistant, and high-performance polytetrafluoroethylene plastic; the remaining steps are the same as those in Example 2.
[0029] Comparative Example 6 The difference between Comparative Example 6 and Example 2 lies in the difference in step (5). Step (5) is changed to: take 0.2 parts of magnesium oxide, 6 parts of ethanol, and 0.6 parts of cerium nitrate, and obtain an electrophoretic suspension after 30 minutes of ultrasound at 500W and 30kHz; immerse the plastic block in the electrophoretic suspension, use an Au sheet as the anode and a Si substrate as the cathode, electrophoretically deposit for 3 minutes at a voltage of 200V and a cathode-anode distance of 2cm, and dry at 60°C for 3 hours. While drying, bombard the film surface with argon ions, and the incident angle of the ion beam is 45° to the normal of the substrate plane. The ion beam energy is 1keV, and a high-thermal-conductivity, wear-resistant, and high-performance polytetrafluoroethylene plastic is obtained; the remaining steps are the same as those in Example 2.
[0030] Comparative Example 7 The difference between Comparative Example 7 and Example 2 lies in the difference in step (5). Step (5) is changed to: 0.2 parts of magnesium oxide, 6 parts of ethanol, 0.6 parts of cerium nitrate, and 0.2 parts of dodecyltrimethoxysilane are taken, and after being ultrasonicated at 500W and 30kHz for 30 minutes, an electrophoretic suspension is obtained; a plastic block is immersed in the electrophoretic suspension, an Au sheet is used as an anode and a Si substrate is used as a cathode, and electrophoretic deposition is performed for 3 minutes at a voltage of 200V and a distance between the anode and the cathode of 2cm, and then dried at 60°C for 3 hours to obtain a high-thermal-conductivity, wear-resistant, and high-performance polytetrafluoroethylene plastic; the remaining steps are the same as those in Example 2.
[0031] Effect Examples Table 1 below shows the performance analysis results of the high thermal conductivity, wear resistance and high performance polytetrafluoroethylene plastics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.
[0032] Table 1 From the comparison of the wear resistance experimental data of the embodiment and the comparative example, it can be found that the present invention first performs alkali fumigation on the boron nitride, and at the same time, ultrasonic microwaves and gaseous alkaline solutions penetrate and modify the boron nitride under the action of ultrasound, thereby making the surface of the boron nitride rich in hydroxyl groups; then, methyl bromoacetate is used to modify graphene oxide to prepare carboxylated graphene, which is then mixed and ground with the modified boron nitride, and a silane coupling agent is continuously added during the grinding process to reduce friction and improve the wear resistance; the prepared modified graphene oxide is mixed with polytetrafluoroethylene and cold-pressed into a plastic, and a magnesium oxide-containing film is prepared on the plastic surface by electrophoretic deposition, and dodecyltrimethoxysilane and electrolyte cerium nitrate are added to the electrolyte solution to react together to form cerium dioxide, and the coating is The micro-cracks are sealed to achieve a wear-resistant effect; from the comparison of the experimental data on heat dissipation of the embodiment and the comparative example, it can be found that the graphene oxide with excellent heat dissipation performance is selected and mixed with boron nitride as a filler to improve its heat dissipation performance, and then a second grinding is performed, and supercritical carbon dioxide is used to assist, so that the boron nitride and graphene oxide are more firmly and evenly combined, while also improving the phenomenon that graphene oxide is easy to agglomerate, so that the plastic performance is better; from the comparison of the experimental data on hydrophobicity of the embodiment and the comparative example, it can be found that the present invention adds silane to the electrophoretic fluid so that the surface of the composite coating has many short rod-shaped protrusions, thereby achieving a hydrophobic effect, and then uses ion beam bombardment to modify the film surface, thereby improving the density of the film and further improving the hydrophobicity of the film.
[0033] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be encompassed therein. Any reference in a claim should not be construed as limiting the claim to which it relates.
Claims
1. A high thermal conductivity, wear-resistant and high-performance polytetrafluoroethylene plastic, characterized in that: The high thermal conductivity, wear-resistant and high-performance polytetrafluoroethylene plastic is prepared by mixing modified graphene oxide as a filler with polytetrafluoroethylene and cold pressing, and then coating a composite film on the outside; the preparation method of the high thermal conductivity, wear-resistant and high-performance polytetrafluoroethylene plastic comprises the following preparation steps: (1) Add 3 parts of boron nitride to 20 parts of deionized water, stir at 250 r / min for 20 min, and ultrasonically treat at 80 °C, 150 W, and 40 kHz. At the same time, spray gaseous sodium hydroxide solution at a flow rate of 4 mL / min and a mass fraction of 10% for 50 min. Then wash with deionized water for 3 times and dry at a vacuum degree of 20 Pa and 60 °C for 5 h to obtain modified boron nitride. (2) 11 parts of graphene oxide and 20 parts of deionized water were ultrasonically dispersed at 100 W and 30 kHz for 1 hour, 0.3 parts of methyl bromoacetate were added, and ultrasonically dispersed at the same conditions for 15 minutes, and the reaction was continued for 5 hours. The filtrate was filtered and washed with deionized water for 3 times, and dried at a vacuum degree of 20 Pa and 50°C for 2.5 hours to obtain carboxylated graphene; (3) Disperse 0.3 parts of carboxylated graphene and 0.2 parts of modified boron nitride in 20 parts of N-methylpyrrolidone solvent, ultrasonicate at 1400W for 1.75h, centrifuge at 4000rpm for 0.75h, and take the solid precipitate to obtain the composite material; put 10 parts of the composite material into a ball mill, add 0.4 parts of 3-triethoxysilyl-1-propylamine three times, add one third of the total amount each time, and add once every 6 hours, use zirconium oxide as the ball medium, 500r / min, and the material-ball ratio is 1:10 for 18 hours, and then dried at 25°C for 12 hours to obtain a ball-milled product; take 5 parts of the ball-milled product and 1.5 parts of a methanol solution, in which the mass ratio of methanol to deionized water is 4:1, stir at 500r / min for 20 minutes, place in a 35°C oil bath, fill with carbon dioxide, increase the temperature and pressure to 120°C and 6.5MPa, react for 2 hours, cool to room temperature, take the precipitate, wash it with methanol 5 times, and dry it at 60°C and a vacuum degree of 20Pa for 6 hours to obtain modified graphene oxide; (4) After 14 parts of polytetrafluoroethylene and 1.5 parts of modified graphene oxide were stirred at 1500 r / min for 30 min, cold pressed at 2.5°C, placed in a mold at 370°C, pressurized to 160 MPa, sintered for 2 h, cooled to 90°C, taken out, and naturally cooled to 25°C to form a plastic cube of 1 cm×1 cm×1 cm; (5) Take 0.2 parts of magnesium oxide, 6 parts of ethanol, 0.6 parts of cerium nitrate, and 0.2 parts of dodecyltrimethoxysilane, and after ultrasonic treatment at 500 W and 30 kHz for 30 minutes, an electrophoretic suspension is obtained; a plastic block is immersed in the electrophoretic suspension, and an Au sheet is used as the anode and a Si substrate is used as the cathode. Electrophoretic deposition is performed for 3 minutes at a voltage of 200 V and a distance between the anode and cathode of 2 cm, and the block is dried at 60°C for 3 hours. While drying, the membrane surface is bombarded with argon ions. The incident angle of the ion beam is 45° to the normal of the substrate plane, and the ion beam energy is 1 keV, thereby obtaining a high-performance polytetrafluoroethylene plastic with high thermal conductivity and wear resistance.